2015
DOI: 10.1007/s13277-015-4019-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miR-940 may serve as a novel biomarker for gastric cancer

Abstract: It was reported that circulating microRNAs could be applied as non-invasive biomarkers for cancer monitoring. The purpose of this study was to identify plasma miRNA that may serve as a novel biomarker for gastric cancer and to evaluate its clinical application. MicroRNA profiles were generated from plasma samples of 5 patients with gastric cancer (GC) versus 5 healthy controls (HC). MicroRNA-940 (miR-940) was one of the most downregulated miRNAs with fold change of 0.164. It was revealed that the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…The expression levels of miRNAs vary by cell type and condition. Thus, in referring to the literature, we found that the overexpressions of miR-940 in pancreatic carcinoma (26) and gastric cancer (27) were correlated with tumor progression. However, the role of miR-940 in ovarian cancer is unknown.…”
Section: Hypoxia Induces Overexpression Of Mir-940 Both In Eoc Cells mentioning
confidence: 68%
“…The expression levels of miRNAs vary by cell type and condition. Thus, in referring to the literature, we found that the overexpressions of miR-940 in pancreatic carcinoma (26) and gastric cancer (27) were correlated with tumor progression. However, the role of miR-940 in ovarian cancer is unknown.…”
Section: Hypoxia Induces Overexpression Of Mir-940 Both In Eoc Cells mentioning
confidence: 68%
“…Ectopic expression of miRNA-133a inhibited GC cell proliferation, migration, and invasion, and induced cell apoptosis [33]. Decreased plasma miRNA-940 may serve as a novel diagnostic biomarker for GC [34]. Overexpression of miRNA-23b-3p reversed GC cell resistance to multiple chemotherapeutics in vitro [35].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hepatocellular carcinoma and low miR-940 expression levels exhibited poorer prognosis compared with high expression levels (18). miR-940 was additionally demonstrated to be downregulated in prostate (20), breast (21) and ovarian cancer (22); however, miR-940 expression was observed to be upregulated in gastric cancer tissues, cell lines and plasma (25). High miR-940 expression levels were strongly correlated with the advanced N stage of gastric cancer (19).…”
Section: Discussionmentioning
confidence: 94%
“…MicroRNAs (miRNAs) comprise a series of endogenous, short single-stranded non-coding RNAs (19)(20)(21)(22)(23)(24)(25) molecules) that primarily serve as gene regulators (8). These molecules negatively regulate gene expression by directly binding to partial complimentary sites in the 3'-untranslated regions (3'-UTRs) of their target genes, resulting in mRNA degradation or inhibition of translation (9).…”
Section: Introductionmentioning
confidence: 99%